Cohort-based programs facilitate skill development and community building for postdoctoral scholars: a pilot study - Nguyen, Karena H. (Frontiers in Education, 2024)
Objective: Postdoctoral scholars ("postdocs") occupy a distinct academic stage and therefore have unique career and professional development needs. We aimed to explore whether a cohort-based program could promote skill development, support career preparation, and facilitate community building among postdocs at our institution. Methods: We applied the design thinking process, commonly used in engineering and industrial design, to create a four-month long leadership and project management program. Pre-and postsurveys with Likert-scale questions measured participants' self-confidence in and self-assessment of competencies related to leadership and project management (e.g., creating an inclusive environment, developing a project charter). Results: Fourteen postdocs from STEM and humanities disciplines participated in the pilot program. Matched responses from participants indicated an 82% positive shift in leadership self-confidence (n = 11) and a 56% positive shift in project management self-confidence (n = 9). Postdocs also showed a positive shift in all 12 competencies related to leadership (n = 11), and a positive shift in nine of 10 competencies related to project management (n = 9). In the optional open-ended questions provided in the surveys, postdocs articulated that the cohort created an environment to share experiences, safely practice new skills, and discuss their career goals. Conclusion: Applying the principles of design thinking to develop a cohort-based professional development program resulted in participant learning gains and their feedback suggests that the program supported a greater sense of belonging. Administrators could use our approach to innovate programming that meets the professional and personal needs of postdocs at their institution.